Insilico Identification of Potent Inhibitor from Andrographis Paniculata for ESBLs - Aysha NIL Mohamed; Mumtaj Peer Mohammed; Dhamotharan R (International Journal of Advances in Applied Sciences, 2014)
The study aimed at docking of TEM - 52 & modeled CTX – M -13 by ethanol extracted compounds from Andrographis paniculata and to predict their binding efficiency. BLAST-P was performed to retrieve suitable templates for homology-modeling using the bla CTX-M sequences obtained from Genbank.  Protein Data Bank (PDB) IDs of these templates were retrieved. Models were prepared using Swiss-Model-Server and verified by Procheck and 3D programmes RAMPAGE was used to prepare Ramachandran plots.   The 13 - Hexyl - oxa - cyclotridec - 10 - En- 2 - one was selected as ligand for this docking study from the data generated by Mass spectrometry analysis of methanol extracted compounds from Andrographis paniculata. The structure was drawn manually with aid of JME and its drug likeliness & molecular properties was calculated using Pre Admet server.  Docking was performed by using docking server. Since the docking results proved that the amino acid residues Ser70,Ser 130,Ser237,Arg 276 and Thr235 of CTX-M-13 (enzyme) make important contacts with the ligand, researchers are expected to duly utilize this information for designing more potent and CTX - M inhibitors.